Horizon of Expectation on Popular Lyrical Poetry: Jauss’s Reader Response Perspective - Alfa Ghifari; Budi Tri Santosa; Diana Hardiyanti (Universitas Muhammadiyah Jember, 2021)
Humans have various opinions in commenting on a literary work. This diversity of opinions will eventually participate in developing research in the literary world. Lyrics are a medium for an author to convey the message he wants to convey in a more free and elegant form. This study aims to describe the reader's perception of the messages and values contained in the lyrics of Rebel's Girl from Bikini Kill, Beyonce from Partition, and God Is a Woman from Ariana Grande. This study uses Jauss' theory of the Harapan Horizon where the role of the reader is the main key in conducting an investigation of a literary work. This research is a qualitative descriptive literature research using a questionnaire distributed to readers who are used as respondents. Respondents were selected randomly with the aim of knowing the differences in opinion of each respondent in responding to a literary work. The conclusion of this study is that the various opinions obtained are influenced by the diversity of backgrounds of the respondents such as differences in gender, age, level of education and experience. In addition, there are messages obtained by readers through the lyrics, namely; freedom of speech, feminism, inner beauty, and sex education.